Abdominal tuberculosis in a spigelian hernia. Issue 5 (15th May 2019) - Aalling, Lisa; Penninga, Luit
Abstract : Abdominal tuberculosis is a common form of extrapulmonary tuberculosis. Often it is difficult to diagnose due to vague symptoms and lack of clinical findings. Spigelian hernia is a rare type of hernia located in the semilunar fascia of the abdominal rectus muscular sheath. We report on a 19-year-old Greenlandic Inuit man with a spigelian hernia as the primary presentation of abdominal tuberculosis. Abdominal tuberculosis presenting with a spigelian hernia is extremely rare, and the case illustrates that tuberculosis may present in myriad ways. The incidence of tuberculosis in Greenland is among one of the highest in the world, and we also review the history and incidence of tuberculosis in this Arctic country.